EGFET pH Sensor Performance Dependence on Sputtered TiO2 Sensing Membrane Deposition Temperature. (18th August 2016) - Yusof, Khairul Aimi; Abdul Rahman, Rohanieza; Zulkefle, Muhammad AlHadi; Herman, Sukreen Hana; Abdullah, Wan Fazlida Hanim
Abstract : Titanium dioxide (TiO2 ) thin films were sputtered by radio frequency (RF) magnetron sputtering method and have been employed as the sensing membrane of an extended gate field effect transistor (EGFET) for pH sensing detection application. The TiO2 thin films were deposited onto indium tin oxide (ITO) coated glass substrates at room temperature and 200°C, respectively. The effect of deposition temperature on thin film properties and pH detection application was analyzed. The TiO2 samples used as the sensing membrane for EGFET pH-sensor and the current-voltage ( I-V ), hysteresis, and drift characteristics were examined. The sensitivity of TiO2 EGFET sensing membrane was obtained from the transfer characteristic ( I-V ) curves for different substrate heating temperatures. TiO2 thin film sputtered at room temperature achieved higher sensitivity of 59.89 mV/pH compared to the one deposited at 200°C indicating lower sensitivity of 37.60 mV/pH. Moreover the hysteresis and the drift of TiO2 thin film deposited at room temperature showed lower values compared to the one at 200°C. We have also tested the effect of operating temperature on the performance of the EGFET pH-sensing and found that the temperature effect was very minimal.